2019
DOI: 10.1007/s11012-019-01056-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of self-organising bubble departures from twin nozzles

Abstract: The nonlinear dynamics of self-organising bubble departures from twin nozzles in engine oils was analysed. Air bubbles were generated from twin brass nozzles with an inner diameter equal to 1 mm. The flow of bubbles in bubble chains was recorded using high-speed camera. The time series of air pressure oscillations and signal from laser-phototransistor identifying the presence of bubbles over the nozzles outlet were recorded simultaneously. The self-organising bubble departures were observed and their stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It can, thus, be inferred that it is the existence of the adjacent active site that causes the deviation of bubble trajectories and makes the bubbles move closer to each other. In the experiment of the isothermal bubble generation system by Dzienis et al, 31 the same trajectories were also observed to show that the bubbles departed from the twin sources attracted each other and moved ward into a single chain.…”
Section: Self-organized Bubble Trajectories From Two Nucleation Sitesmentioning
confidence: 62%
“…It can, thus, be inferred that it is the existence of the adjacent active site that causes the deviation of bubble trajectories and makes the bubbles move closer to each other. In the experiment of the isothermal bubble generation system by Dzienis et al, 31 the same trajectories were also observed to show that the bubbles departed from the twin sources attracted each other and moved ward into a single chain.…”
Section: Self-organized Bubble Trajectories From Two Nucleation Sitesmentioning
confidence: 62%
“…In this method, subsequent coordinates of attractor points are calculated based on the samples between which the distance is equal to the time delay (τ). The proper value of time delay (τ) was estimated using the following criterion [20]: ( )~0.5 (0) (7) with the autocorrelation function, (Ca) of the form given by [18]:…”
Section: Priodicity Of Bubble Departuresmentioning
confidence: 99%
“…The chaotic nature of bubble departure has been extensively investigated [4,5,6,7,8], and from these investigations it can be concluded that two groups of phenomena are responsible for the occurrence of chaotic bubble departures: the particular dynamics of the bubble flow in the liquid as well as the hydrodynamics of liquid flow around the capillary [4,8,9,10] and the erratic changes of pressure in the gas supply system that accompany this flow [4,5,9,12,13]; these phenomena are connected with the nonlinear dynamics of the capillary filling process. These dynamics are sensitive to the physical and chemical properties of the two-phase system, notably the viscosity and surface tension, and to the container geometry and have been previously investigated [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the processes of bubble formation, bubble flow and its stability. The experimentally and numerically investigations of the bubble formation [1,6], bubble coalescence [7,8], gas bubble trajectories [9,10] or chaotic bubble behaviours [11][12][13] are still conducted.…”
Section: Introductionmentioning
confidence: 99%